2012
DOI: 10.1093/toxsci/kfs275
|View full text |Cite
|
Sign up to set email alerts
|

Clear Evidence of Carcinogenic Activity by a Whole-Leaf Extract of Aloe barbadensis Miller (Aloe vera) in F344/N Rats

Abstract: Aloe barbadensis Miller (Aloe vera) is an herbal remedy promoted to treat a variety of illnesses; however, only limited data are available on the safety of this dietary supplement. Drinking water exposure of F344/N rats and B6C3F1 mice to an Aloe vera whole-leaf extract (1, 2, and 3%) for 13 weeks resulted in goblet cell hyperplasia of the large intestine in both species. Based upon this observation, 2-year drinking water studies were conducted to assess the carcinogenic potential of an Aloe vera whole-leaf ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 73 publications
2
78
1
2
Order By: Relevance
“…Among them, Aloe vera (L.) Burm.f. (Aloaceae) (aloe) is a genus of medicinal plants with a history of medical use for several thousand years (Boudreau et al, 2013;Harlev et al, 2012). Its antineoplastic property is due to at least three different mechanisms based on antiproliferative, immunostimulatory, and antioxidant effects, whereas the antiproliferative action is determined mainly by the anthraquinonic molecules, such as aloin and emodin (Harlev et al, 2012).…”
Section: Herbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, Aloe vera (L.) Burm.f. (Aloaceae) (aloe) is a genus of medicinal plants with a history of medical use for several thousand years (Boudreau et al, 2013;Harlev et al, 2012). Its antineoplastic property is due to at least three different mechanisms based on antiproliferative, immunostimulatory, and antioxidant effects, whereas the antiproliferative action is determined mainly by the anthraquinonic molecules, such as aloin and emodin (Harlev et al, 2012).…”
Section: Herbsmentioning
confidence: 99%
“…However, only limited data are available on the safety of Aloe vera supplements leaving this issue controversial and uncertain. Few reports have even shown that aloe leaf extract can itself exert some carcinogenic activity (Ahlawat & Khatkar, 2011;Boudreau et al, 2013). Aloin and aloe emodin were found in roots and petioles of Rheum rhaponticum L. (Polygonaceae) (dietary rhubarb) cultivated in Estonia, but not mentioned in folk medicine as the anticancer herbal remedy (Püssa et al, 2009).…”
Section: Herbsmentioning
confidence: 99%
“…In such regard, the conduct of long-term carcinogenicity/toxicity studies of natural products should not be minimized as proven by the recent demonstration of the carcinogenic effects of kava and aloe vera extracts for increasing hepatocellular and lower bowel (adenomas and carcinomas) tumors, respectively, in rats. [61][62][63][64] We believe, therefore, that the conduct of long-term carcinogenicity/toxicity studies of natural products, mainly those used for years, should be encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…44 Aloe vera latex extracted from the outer leaf pulp contains anthraquinones, mainly as aloins, which have been shown to produce a laxative effect, 39 but are carcinogenic in animal models. 45 Because of such safety concerns, since 2002, the FDA has banned the use of Aloe vera latex in over-the-counter laxative products. 46 The Natural Medicines Comprehensive Database warns against the oral ingestion of Aloe vera latex because it is likely unsafe for use by adults and children.…”
Section: Aloe Vera Gelmentioning
confidence: 99%